Indelible city : dispossession and defiance in Hong Kong - Lim, Louisa (Riverhead Books, 2022)
"An award-winning journalist and longtime Hong Konger indelibly captures the place, its people, and the untold history they are claiming, just as it is being erased. Lim's deeply researched-and deeply personal-account casts often startling new light on key moments: the British takeover in 1842, the negotiations leading to its "return" to China in 1997, the current protests, and the future Beijing seeks to impose. Throughout, it is populated by contemporary figures who, like her, aim to put Hong Kongers at the center of their own story: guerrilla calligraphers, amateur historians and archaeologists, and wending through it all, the King of Kowloon, a mentally ill trash collector, descended from royalty, whose iconic street art both embodied and inspired the unique identity Lim unforgettably conveys-Hong Kong as a place of disappearance and reappearance, power and powerlessness, loss and reclamation, silence and voice"--